2016
DOI: 10.1177/1523422316641417
|View full text |Cite
|
Sign up to set email alerts
|

Influences of an Evangelical Christian Worldview on Women’s Leadership Development

Abstract: The Problem A recent Pew Research Center report noted that 70.6% of U.S. American adults self-identify as Christian; 25.4% identify themselves as Protestant Evangelical. Historically, the worldview of evangelicals has reflected what Gallagher described as a “hierarchically ordered universe.” The implications of this worldview on both individuals and organizational cultures add complexities as women navigate the labyrinth of leadership. Such complexities, related to the implied superiority of maleness, call for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…An analysis of this subset of private colleges and universities by Dahlvig and Longman (2016) in relation to women's leadership development identified that "individuals adhering to an evangelical worldview may view leadership-either consciously or subconsciously-through a set of presuppositions that is detrimental to women's advancement into leadership roles" (p. 244). Although it is clear that evangelicalism in the U.S. (let alone worldwide) is not monolithic, some streams of thought within evangelicalism understand there to be God-ordained gender roles in marriage, the church, and (in fewer cases) society in general.…”
Section: Theological Commitments and Women's Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of this subset of private colleges and universities by Dahlvig and Longman (2016) in relation to women's leadership development identified that "individuals adhering to an evangelical worldview may view leadership-either consciously or subconsciously-through a set of presuppositions that is detrimental to women's advancement into leadership roles" (p. 244). Although it is clear that evangelicalism in the U.S. (let alone worldwide) is not monolithic, some streams of thought within evangelicalism understand there to be God-ordained gender roles in marriage, the church, and (in fewer cases) society in general.…”
Section: Theological Commitments and Women's Leadershipmentioning
confidence: 99%
“…In some cases, participants struggled to reconcile the institutional view of an "ideal" woman with their own identities. The push and pull factors represent aspects of the literature of gendered leadership (Diehl and Dzubinski 2016;Egan et al 2017;Ibarra et al 2013;Kellerman and Rhode 2014), as well as circumstances unique to Christian higher education (Dahlvig and Longman 2016;Joeckel and Chesnes 2009;Reynolds 2014).…”
Section: Grounded Theory Modelmentioning
confidence: 99%
“…This neglect might reflect the paucity of women congregants in senior leadership roles in most religious organizations, especially ones that adhere to patriarchal norms (Cnaan & Helzer, 2004; Ecklund, 2006; Ojong, 2017; Stolz & Monnot, 2019; Wallace, 2000). Although there are other women‐only settings for leadership development in nonreligious organizations (Archard, 2012; Häyrynen & Lämsä, 2017; Levin, 2011), it is important to explore whether and how faith‐driven beliefs in traditional gender roles in religious settings relate to women's potential to transfer leadership learning (Cnaan & Helzer, 2004; Dahlvig & Longman, 2016; Longman, Drennan, Beam, & Marble, 2019; Ojong, 2017). The current exploratory study can provide insight on potential for women to transfer leadership learning from life experiences, resulting in broader understanding about how to reduce gender leadership gaps.…”
Section: Significance Of Studymentioning
confidence: 99%
“…In addition, because men typically dominate leadership roles, particularly in traditional churches, little is known about how this type of leadership learning transfer might occur for women volunteers in religious settings (Cnaan & Helzer, 2004; Dahlvig & Longman, 2016; Ecklund, 2006; Longman et al, 2019; Ojong, 2017; Stolz & Monnot, 2019; Wallace, 2000). For instance, some literature has highlighted how when women from patriarchal societies embark on experiences such as migration endeavors, that require more independence and exposure to broader contexts in the world, their perspectives can change in a way that might make them more likely to contribute professionally and civically in communities (Lee, 2013; Yang & Ren, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation